R-(+)-limonene diastereoselective epoxidation: A minireview about of the synthesis methods - Rubio Rodríguez, Juan Alejandro; Jairo Antonio (Universidad Pedagógica y Tecnológica de Colombia, 2022)
R-(+)-limonene epoxidation has been focused from different synthesis methods. Thanks to the optically active epoxides obtained from this reaction are widely employed at industrial level, like: agrochemicals, polymers, cosmetics, pharmaceuticals. A key point found in this topic has been the asymmetric induction to improve the yield to the diastereomers of 1,2-limonene oxide. Many catalysts have been developed for the diastereoselective epoxidation, but some oxidation methodology have not been so useful. The enzymes and the Jacobsen´s catalyst presented the highest selectivity towards the endocyclic epoxides diastereomers, while other catalysts like metals supported on mesoporous materials were directed to one or more oxidation products, reducing their potential industrial scaling. Also, it was evidenced that controlling the reaction parameters it allows the segregation homogeneous catalyst to a phase different from the reaction products, thus increasing its useful reutilization in several reaction cycles. This minireview confronts the different systems used for the diastereoselective epoxidation of R-(+)-limonene. Challenges, issues and trends of said chemical transformation are also discussed.